A Chiral N, N′‐Dioxide–ZnII Complex Catalyzes the Enantioselective [2+2] Cycloaddition of Alkynones with Cyclic Enol Silyl Ethers. (25th April 2016) - Kang, Tengfei; Ge, Shulin; Lin, Lili; Lu, Yan; Liu, Xiaohua; Feng, Xiaoming
Abstract: A highly efficient enantioselective [2+2] cycloaddition between alkynones and cyclic enol silyl ethers was developed by using a chiral N, N′ ‐dioxide‐zinc(II) complex as a catalyst. This method functions well for a variety of terminal alkynes as well as cyclic enol silyl ethers, with good to excellent enantioselectivity (up to 97 % ee ). This is also the first successful example for the catalytic enantioselective [2+2] cycloaddition of internal alkynes with cyclic enol silyl ethers to give fully substituted cyclobutenes. Meanwhile, the desired cyclobutene product can easily be transformed into fused cyclobutane derivatives. Abstract : Kondensierte Cyclobutene : Die Titelreaktion mit einem chiralen N, N′ ‐Dioxid/Zn(NTf2 )2 ‐Katalysator setzt eine Vielzahl von endständigen Alkinen hoch enantioselektiv mit cyclischen Silylenolethern um. Interne Alkine liefern vollständig substituierte Cyclobutene. TBS= tert ‐Butyldimethylsilyl.